Forming a learning environment using social cloud services - V. H. Hrytsenko (CTE Workshop Proceedings, 2013)
Current educational processes are unthinkable without the use of information technology. This demand for them forces educational institutions to constantly increase the financial cost of purchasing and maintaining hardware and software. The problem can be partially helped by cloud services, which under certain conditions allow you to save money by directing them only to pay for cloud services, and in the case of using free services - mainly for the educational process. Already now, cloud providers offer quite reliable services to educational institutions for free or for a small fee. The most active providers of cloud services for education globally are Google and Microsoft. They provide educational institutions with a number of free communication tools, such as email, task manager, data storage, word processing, spreadsheet, presentation, etc.